DAMPAK MEKANISASI PERTANIAN TERHADAP PENDAPATAN BURUH TANI WANITA DI DESA SUNGAI DUA KECAMATAN RAMBUTAN KABUPATEN BANYUASIN - reshi wahyuni; Nurlaili Fitri Gultom; Dewi Meidalima; Chuzaimah Chuzaimah (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2022)
This study aims Calculate the work out time, the income of female farm labourer on swamp rice fields, and to analyze the impact of agricultural mechanization to the work out time and income of female farm labourer on swamp rice field. The research method was used survey method and sampling method was a simple random sampling. The data were processed by tabulation and analyzed quantitatively by a paired sample t-test. The result showed that the work out time of female farm labourer before agricultural mechanization was 49.70 HOK per year and after agricultural mechanization decreased to 16.08 HOK per year. Meanwhile, the average income of female farm labourer before agricultural mechanization was Rp. 3.454.333 per year and the average income after agricultural mechanization is Rp. 1.043.667,- per year. This showed that there was a decrease in the income of female farm labourer in rice fields in Sungai Dua Village after the mechanization of agriculture, which amounted to Rp. 2.410.666 per year. The results of the t test showed that there were differences in work out time and income of female farm labourer on rice field activities before and after agricultural mechanization.